Assessing quality and reliability of online videos on tachycardia: a YouTube video-based study - Zexi Li; Chunyi Yan; Xiaojun Lyu; Fanghui Li; Rui Zeng (BMC, 2024)
Abstract Background Considering the adverse clinical consequences of pathologic tachycardia and the potential anxiety caused by physiological tachycardia in some heathy individuals, it is imperative to disseminate health information related to tachycardia for promotion in early diagnosis and appropriate management. YouTube has been increasingly used to access health care information. The aim of this study is to assess the quality and reliability of English YouTube videos focusing on tachycardia and further delve into strategies to enhance the quality of online health resources. Methods We conducted a search using the specific key words "tachycardia" in YouTube online library on December 2, 2023. The first 150 videos, ranked by "relevance", were initially recorded. After exclusions, a total of 113 videos were included. All videos were extracted for characteristics and categorized based on different topics, sources or contents. Two independent raters assessed the videos using Journal of American Medical Association (JAMA) benchmark criteria, Modified DISCERN (mDISCERN) tool, Global Quality Scale (GQS) and Tachycardia-Specific Scale (TSS), followed by statistical analyses. All continuous data in the study were presented as median (interquartile range). Results The videos had a median JAMA score of 2.00 (1.00), mDISCERN of 3.00 (1.00), GQS of 2.00 (1.00), and TSS of 6.00 (4.50). There were significant differences in JAMA (P < 0.001), mDISCERN (P = 0.004), GQS (P = 0.001) and TSS (P < 0.001) scores among different sources. mDISCERN (P = 0.002), GQS (P < 0.001) and TSS (P = 0.030) scores significantly differed among various contents. No significant differences were observed in any of the scores among video topics. Spearman correlation analysis revealed that VPI exhibited significant correlations with quality and reliability. Multiple linear regression analysis suggested that longer video duration, sources of academics and healthcare professionals were independent predictors of higher reliability and quality, while content of ECG-specific information was an independent predictor of lower quality. Conclusions The reliability and educational quality of current tachycardia-related videos on YouTube are low. Longer video duration, sources of academics and healthcare professionals were closely associated with higher video reliability and quality. Improving the quality of internet medical information and optimizing online patient education necessitates collaborative efforts.